Social tolerance for human diversity in Sub-Saharan Africa - Bangwayo-Skeete, P.F.; Zikhali, Precious (Emerald Publishing Limited, 2011)
Purpose - This paper seeks to investigate the individual-level determinants of self-declared social tolerance towards six groups/practices in Sub-Saharan Africa (SSA): tolerance to linguistic differences, racial distinction, religious dissimilarity, homosexuality, acquired immuno deficiency syndrome (AIDS) victims and immigrants. Design/methodology/approach - Using individual-level data from the 2005 World Values Survey, the paper simultaneously estimates multivariate probit models for all six dimensions of social tolerance. Findings - Apart from the strong interdependency among all social tolerance indicators, the analysis reveals that individual attributes affect tolerance towards the six groups differently. For instance, education enhances social tolerance for all groups except homosexuals while access to media increase tolerance for people living with AIDS. Research/limitations/implications - Effective social tolerance policies can be enhanced through joint targeting of the indicators considered. Moreover, tolerance-enhancing policies generally benefit from improved access to education while improved access to media could increase tolerance for AIDS victims. Originality/value - The originality of the analysis lies in the joint analysis or determination of a wider spectrum of social tolerance indicators. This paper can help to inform policies that are aimed at reducing SSA's recurrent inter- and intra-group conflicts attributed primarily to the region's high levels of ethnic and cultural fragmentation.